MODERNISING SYARIAH CRIMINAL JUSTICE: THE IMPERATIVE OF DIGITAL FORENSIC SCIENCE AND EVIDENTIARY REFORM IN MALAYSIA (International Seminar on Syariah and Law (INSLA), 2025)
The rapid evolution of science and technology has fundamentally transformed the landscape of modern criminality, leading to a rise in cyber offences that challenge the traditional boundaries of the Malaysian Syariah criminal justice system. As criminal activities migrate to the digital realm, the reliance on conventional evidence is increasingly being supplemented by digital footprints. However, the integration of digital evidence faces significant hurdles, primarily due to the rigid requirements of classical evidentiary methods such as iqrar (confession) and shahadah (eyewitness testimony), which are often unattainable in anonymous virtual environments. Furthermore, the lack of standardised procedural guidelines for handling electronic data creates a legal lacuna that may jeopardize the admissibility of such evidence. This study therefore aims to evaluate the role and significance of digital forensics as a form of qarīnah muʻāșirah (contemporary circumstantial evidence) within the Syariah legal framework. Adopting a qualitative research design, this study utilises document analysis to examine relevant literature and legal texts. The gathered data is then analysed and presented through a thematic approach, categorising findings into key themes. The findings indicate that digital forensics, through rigorous processes such as cryptographic hashing and the “chain of custody”, provides a scientifically objective basis for proof that aligns with the Syariah principle of yaqin (certainty). The study highlights that the technical capabilities of modern forensic tools can effectively reconstruct digital events and establish intent (niyyah) in cyber-crimes. This research is significant as it provides a fundamental bridge between forensic science and Islamic jurisprudence, offering insights for policymakers to reform existing evidence laws. In sum, the recognition of digital forensics as a robust form of qarinah is essential to ensure that the Syariah courts remain dynamic, equitable, and responsive to the complexities of the digital age.